Advancing lithium metal electrode beyond 99.9% coulombic efficiency via super-saturated electrolyte with compressed solvation structure - Wujie Yang; Aoyuan Chen; Ping He; Haoshen Zhou (Nature Communications)
Abstract Lithium metal negative electrode is pivotal for advancing high-energy-density lithium batteries. Despite their promise, the inherent poor interfacial stability of electrolytes on lithium metal and the repeated reconstruction of the solid electrolyte interphase lead to continuous consumption of active Li and electrolyte, causing rapid failure of Li metal batteries under practical conditions. Here, we propose compressing the spacing between Li ions and anions to recruit more anions around Li ions, forming tighter solvation clusters, and then achieving the super-saturated electrolyte with a 16 M Li salt concentration in the solvent phase. This compressed solvation structure electrolyte demonstrates enhanced stability towards Li metal negative electrode, attaining more than 99.9% coulombic efficiency in Li||Cu cells and enabling long cycling life in lean-Li Li metal full cells. Designed with a positive electrode material proportion of 68%, our Li metal pouch cell achieves a specific energy of 510.3 Wh kg−1 (based on the total mass of the cell) and maintains stable cycling over 100 cycles.